Aktivitas Antibakteri Ekstrak Bronok (Acaudina molpadioides) terhadap Pertumbuhan Bakteri Staphylococcus aureus dan Escherichia coli: Antibacterial Activity of Bronok Extract (Acaudina molpadioides) against the Growth of Staphylococcus aureus and Escherichia coli Bacteria - Suhaera Suhaera; Aprilya Sri Rachmayanti; Nadya Aoliyaninda (Jurnal Surya Medika (JSM), 2022)
Bronok (Acaudina molpadioides) is a type of marine biota of the phylum Echinoderms class Holothuroidea that can empirically increase stamina and have positive effects on health. One of the infectious diseases such as diarrhea is caused by Escherichia coli and Staphylococcus aureus bacteria which are still a major problem in public health and have the potential to cause death. Most of these bacteria have developed resistance to antibiotics This study aims to determine the antibacterial activity of extracts of bronchus (Acaudina molpadioides) against the growth of Staphylococcus aureus and Escherichia coli bacteria. In addition, this study uses the disc diffusion method with concentrations of 25%, 50% and 75% with the sample used is bronchoconstriction extract. The results of the bland zone diameter showed that methanol extract was able to inhibit the growth of Staphylococcus aureus bacteria with an average diameter of 4.1 mm, 5.3 mm, and 5.8 mm, ethyl acetate extract which is 4.7 mm, 6.2 mm, and 15.2 mm. Methanol extract showed resistance to Escherichia coli bacteria with an average diameter of 3.7 mm, 4.5mm, and 5 mm. The results of the bronok extract study (Acaudina molpadioides) had antibacterial activity against Staphylococcus aureus bacteria in methanol and ethyl acetate extracts. Methanol extract has antibacterial activity against Escherichia coli bacteria. By looking at the inhibition zone of each solvent where the larger the inhibition zone, the stronger the antibacterial activity.